Laboratory observations on predator–prey interactions between the bearded fireworm (Hermodice carunculata) and Mediterranean benthic invertebrates. Issue 3 (4th May 2018) - Simonini, Roberto; Maletti, Isabella; Righi, Sara; Fai, Sergio; Prevedelli, Daniela
ABSTRACT: The bearded fireworm ( Hermodice carunculata ) is an amphinomid polychaete with a circumtropical Atlantic-Mediterranean distribution. In the Mediterranean Sea, very little information is available on its feeding habits and ecological functions. Here, its increasing abundance and the ability to actively prey on a keystone sea urchin species suggest potential repercussions for the structure and functioning of benthic communities. We performed laboratory feeding experiments to investigate interactions between Mediterranean H. carunculata and 12 species of sessile or sedentary invertebrates. H. carunculata preyed efficiently on 9 of the species offered. In particular, active predation of a polychaete upon nudibranchs, colonial ascidians and chitons was reported for the first time. Fireworms' predatory ability may be due to a combination of several 'weapons' (large size, motility, stinging chaetae and eversible, sucking pharynx) which seems to be unique among marine worms, and could enable H. carunculata to persist also after radical changes in prey community composition and withstand selective pressures associated with ongoing environmental changes.